2020
DOI: 10.1177/0961203320962855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on patients with systemic lupus erythematosus: Observations from an Indian inception cohort

Abstract: Introduction The ongoing pandemic of COVID-19 has led to severe disruption of healthcare services worldwide. We conducted this study to assess the impact of COVID-19 pandemic on the management of Systemic Lupus Erythematosus (SLE) patients who were enrolled in the nation-wide inception cohort. Methods A questionnaire was administered to the SLE patients enrolled in the inception cohort. Questions related to the effect on disease activity, preventive measures adopted against COVID-19, the incidence of COVID-19,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
(31 reference statements)
0
34
0
Order By: Relevance
“…During the COVID‐19 pandemic, studies in Asia showed that only 0.1%‐0.2% of SLE patients had documented infection with COVID‐19 85‐89 (Table 5). Together with other case series and reports, there is a total of 18 reported SLE patients with COVID‐19 infection 90‐94 .…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID‐19 pandemic, studies in Asia showed that only 0.1%‐0.2% of SLE patients had documented infection with COVID‐19 85‐89 (Table 5). Together with other case series and reports, there is a total of 18 reported SLE patients with COVID‐19 infection 90‐94 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, only D 1 8 2 X X2 patients in this study contracted SARS-CoV-2 and both had a mild COVID-19 course. 230 Similarly, in a study of 1040 patients with SLE in India, over 50% of patients had missed their follow-up appointments, 37% were unable to perform routine laboratory exams, 40% needed to change their medications due to lack of availability, and 25% presented financial difficulties during the lockdown period, 231 suggesting additional sources of stressors experienced by these patients.…”
Section: Ancestral Background Socioeconomic Factors and Indirect Conmentioning
confidence: 99%
“…The authors reported that up to 41% of the patients referred difficulty in obtaining hydroxychloroquine and 40.7% of the patients referred disease flare. Non-adherence to treatment has been extensively described in patients with rheumatic diseases during the COVID-19 pandemic and has been attributed to limited access to medications as well as to patients' fears related to immunosuppressive drugs [3,13,19,25,26,28,[30][31][32].…”
Section: Plos Onementioning
confidence: 99%